Barriers facing persons with disability in accessing sexual and reproductive health services in sub-Saharan Africa: A systematic review. - John Kuumuori Ganle; Leonard Baatiema; Reginald Quansah; Anthony Danso-Appiah (PLoS ONE, 2020)
Background There is evidence that persons with disabilities often encounter grave barriers when accessing sexual and reproductive health services. To the best of our knowledge, however, no systematic review has been conducted to pull together these pieces of research evidence for us to understand the nature, magnitude and extent of these barriers in different settings in sub-Saharan Africa. We do not yet have a good understanding of the strength/quality of the evidence that exist on the barriers persons with disabilities face when accessing sexual and reproductive health services in sub-Saharan Africa. We therefore conducted a systematic review to examine the barriers persons with disabilities face in accessing sexual and reproductive health services in sub-Saharan Africa. Methods A systematic review was conducted using PRISMA guidelines (PROSPEROO protocol registration number: CRD42017074843). An electronic search was conducted in Medline, EMBASE, CINAHL, PsycINFO, and Web of Science from 2001 to 2020. Manual search of reference list was also conducted. Studies were included if they reported on barriers persons with disability face in accessing sexual and reproductive health services. The Critical Appraisal Skills Programme and Centre for Evidence Based Management (CEBMa) appraisal tools were used to assess methodological quality of eligible studies. Findings A total of 1061 studies were identified. Only 26 studies covering 12 sub-Saharan African countries were eligible for analysis. A total of 33 specific barriers including inaccessible physical health infrastructure and stigma and discrimination were identified. These barriers were further categorised into five levels: broader national level barriers; healthcare system/institutional barriers; individual level barriers; community level barriers; and economic barriers. Conclusion Persons with disabilities face a myriad of demand and supply side barriers to accessing sexual and reproductive healthcare in sub-Saharan Africa. Multilevel interventions are urgently needed to address these barriers.